Trapping of red palm weevil in coconut gardens - Ramesha B (Department of Agricultural Entomology, College of Horticulture, 1999)
Experiments were undertaken in the Department of Agricultural Entomology, College of Horticulture, Vellanik:kara during 1997-1998 to evaluate the efficacy of the male aggregation pheromone Ferrolure (4-Methyl-5 nonanol) in mass trapping the redpalm weevil of coconut Rhynchophorus ferrugineus F (Oliv.) in the coconut plantations of Thrissur district. A survey was conducted in Thrissur district in three regions representing three geographical zones viz., coconut plantations in coastal zones, midland regions and upland conditions with the respective red palm weevil damage incidence of 5.33 per cent, 7.66 per cent and five per cent with an average incidence of six per cent. A convenient and suitable bucket trap was designed and fabricated for the mass trapping of the adult weevils from the field and for further laboratory experiments. Out of the different food attractants tried pineapple waste and toddy gave increased trapping efficiency of the weevils with the pheromone sachet. The food attractants was necessarily to be renewed afresh once in three to four days interval so as to keep the trap effective. At this rate of change of the food attractant a single pheromone sachet was found to be actively performing to trap the weevils for a period of 10-12 weeks. The Ferrolure tried was found to be predominently a male aggregation pheromone but with reasonable attraction to female weevils as well.